THE EVALUATION OF COVID-19 BLT DISTRIBUTION IN BLITAR REGENCY - Sulistyo Anjarwati; Novita Setyoningrum; Soebiantoro (Universitas Islam Balitar, 2021)
The purpose of this study was to evaluate the distribution of BLT in Blitar Regency could be distributed properly. Then for the better future it is hoped that this research can provide a clearer understanding of the main problems related to the distribution of COVID-19 social assistance so the further research can elaborate on alternative solutions. The research method used is qualitative methods. This study focuses on the evaluation of Cash Transfer for the poor or underprivileged in Blitar Regency. This research activity was carried out in Sumberjo Village, Sutojayan District, Blitar Regency. The result of this research shows Sumberjo Village is one of the villages in Blitar Regency that received the Social Assistance program in the form of Cash Transfer (BLT). The mechanism on data recipients collecting of Cash Transfer (BLT) in Sumberjo Village is carried out in accordance with the regulations from the Ministry of Villages which consist of 14 criteria for the recipients of Cash Transfer (BLT). In addition to being carried out in accordance with the regulations, the mechanism for collecting data on recipients of Cash Transfer (BLT) in Sumberjo Village also considers data from the Ministry of Social Affairs, the Integrated Data for Social Welfare (DTKS). The number of BLT recipients in Sumberjo Village in stage 1 and 2 of 2020 was 23 KPM while in stage 3 was 21 KPM. The process of distributing Cash Transfer (BLT) by the Sumberjo Village Government ran relatively smooth.